2019
DOI: 10.7150/jca.36300
|View full text |Cite
|
Sign up to set email alerts
|

Update on current pancreatic treatments: from molecular pathways to treatment

Abstract: Pancreatic cancer is still diagnosed at a late stage although we have novel diagnostic tools. Pancreatic cancer chemotherapy treatment resistance is observed and therefore novel treatments are in need. Anti-cancer stem cell therapy, combination of chemotherapy and/or radiotherapy with immunotherapy, proteins/enzymes and gene therapy are currently under evaluation. Targeted treatment with tyrosine kinase inhibitors is also administered and novel inhibitors are also under evaluation. In the current review we pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…The MAPK/ERK and PI3K/AKT/mTOR pathways represent major targets for therapeutic intervention of PDAC, and multiple inhibitors of each of the pathways are clinically available (Eser et al, 2014). While drugs that block these pathways are being tested in the clinic, new efforts are underway to exploit previously unrecognized vulnerabilities, such as altered signaling networks, for novel targeted therapies (Ducreux et al, 2019;Sapalidis et al, 2019). Our integration of proteomic and phosphoproteomic measurements revealed that PAK1/PAK2 kinases were upregulated in most PDACs in our cohort (Figure 5) and these kinases have been reported to be critical effectors/regulators of vital signaling pathways that mediate cellular cytoskeletal motility, proliferation, and survival (Zhou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK/ERK and PI3K/AKT/mTOR pathways represent major targets for therapeutic intervention of PDAC, and multiple inhibitors of each of the pathways are clinically available (Eser et al, 2014). While drugs that block these pathways are being tested in the clinic, new efforts are underway to exploit previously unrecognized vulnerabilities, such as altered signaling networks, for novel targeted therapies (Ducreux et al, 2019;Sapalidis et al, 2019). Our integration of proteomic and phosphoproteomic measurements revealed that PAK1/PAK2 kinases were upregulated in most PDACs in our cohort (Figure 5) and these kinases have been reported to be critical effectors/regulators of vital signaling pathways that mediate cellular cytoskeletal motility, proliferation, and survival (Zhou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An explanation behind this is that the pancreatic cancer presents non-specific symptoms, which lead to a delayed diagnosis and dismal prognosis (127). Actual therapies against pancreatic ductal adenocarcinoma include surgery, adjuvant chemotherapy, radiation therapy (intraoperative, in which a large dose of radiation is given to the area at the same time as the surgery, or the proton beam radiation) and targeted therapies (128).…”
Section: Epidemiology and Risk Factors In Pancreatic Cancermentioning
confidence: 99%
“…Therefore, combination therapies with gemcitabine plus nab-paclitaxel or the FOLFIRINOX protocol (a combination therapy containing folinic acid, fluorouracil, irinotecan, and oxaliplatin) are superior compared to the formerly widely used gemcitabine monotherapy (reviewed in [5]). Currently, personalized oncology heads towards specific, targeted (combinatorial) therapies, and also include immunotherapeutic approaches, therapies interfering with cancer stem cells or with distinct cancer-associated pathways or receptors [6,7]. But not only the tumor cell itself may be a target, rather tumor-promoting T cells which among others produce tumor necrosis factor (TNF)-α, interleukin (IL)10, IL17A, IL21, and IL26 [8][9][10][11] as possible targets.…”
Section: Introductionmentioning
confidence: 99%